Perceived susceptibility, barriers, and cues to action as determinant factors of reproductive health behavior - Wahyu Setyaningsih; Ika Yudianti; Herawati Mansur (International Journal of Public Health Science (IJPHS), 2022)
Adolescents are confronted with many reproductive health problems because of unstable conduct. This research aimed to investigate reproductive health behavior in female teens through the usage of a health belief model. This cross-sectional study was conducted in September, 2020 at Madrasah Aliyah Negeri 1 Malang, Indonesia. Data have been collected by questionnaires from 152 female high school students who were selected by simple random sampling. Data were analyzed using logistic regression. The study found that there are relationships among perceived susceptibility, perceived barriers, and cues to action with p<0.001, perceived severity (p 0.012), perceived benefits (p 0.001), and self-efficacy (p 0.008). The goodness of fit test showed that the data fit with the logistic regression model (p 0.917) and 79.7% of reproductive health behavior is associated with these six variables. Perceived susceptibility, barriers, and cues to action as a determinant aspect of reproductive health behavior. Adolescents should have the understanding and motivation to act in a healthy way associated with their reproductive health.